Sleep and REM Behaviour Disorder- Much More than Sleep Walking - Ravindran, Rohini (Trinity Student Medical Journal, 2007)
Rapid eye movement (REM) sleep is characterised by the active neurological processes which underpin dreaming and result in the paralysis of all somatic musculature, except extra-ocular muscles and the diaphragm for continued respiration. Recently, a sleep parasomnia, termed REM Behaviour Disorder (RBD), has been described, in which patients physically act-out their dreams in an excited and sometimes violent manner. This paper presents two clinical vignettes describing patients with RBD and reviews the available literature on the subject.